The Australian Lymexylidae (Coleoptera: Tenerionoidea) with one new genus and two genera new to Australia - Lawrence, John F. (Zootaxa, 2020)
The generic classification of Lymexylidae is reexamined, particularly with reference to the Australian fauna. The transfer of the Madagascar genus and species Alcestoma serropalpoides Fairmaire (1895) from Melandryidae to Lymexylidae, proposed by Nikitsky in Nikitsky et al. (1998), is confirmed and the genus is considered to be a senior synonym of Protomelittomma Wheeler (1986), syn. n. The occurrence of the genus Alcestoma in Australia is noted and a new species, Alcestoma queenslandicum, sp. n. is described from northern Queensland. The genus Arractocetus Kurosawa (1985) is also recorded for the first time from Australia, but the species is not described. A new genus, Leptonetron, gen. n., is described, based on the type species Atractocerus victoriensis Blackburn, 1891, which is considered to be a senior synonym of Atractocerus tasmaniensis Lea, 1917, syn. n. A key is provided for the Australian genera and species of Lymexylidae and the evolution of the family is briefly discussed.